2013
DOI: 10.1186/1745-6215-14-393
|View full text |Cite
|
Sign up to set email alerts
|

A brief intervention for weight management in primary care: study protocol for a randomized controlled trial

Abstract: BackgroundObesity affects 25% of the UK adult population but modest weight loss can reduce the incidence of obesity-related chronic disease. Some effective weight loss treatments exist but there is no nationally available National Health Service (NHS) treatment service, and general practitioners (GPs) rarely discuss weight management with patients or support behavior change. Evidence shows that commercial weight management services, that most primary care trusts have 'on prescription', are more effective than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Although intensive lifestyle interventions are the gold standard for weight loss, 31 a single brief intervention can motivate some patients to change their behavior, 32 and reflects the reality of most primary care settings. Therefore, it is important to determine whether brief interventions provided in primary care can be augmented by strategies such as incorporation of genetic counseling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…Although intensive lifestyle interventions are the gold standard for weight loss, 31 a single brief intervention can motivate some patients to change their behavior, 32 and reflects the reality of most primary care settings. Therefore, it is important to determine whether brief interventions provided in primary care can be augmented by strategies such as incorporation of genetic counseling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…The full trial protocol has been reported previously 15 and is available online. The protocol was implemented without changes.…”
Section: Methodsmentioning
confidence: 99%
“…Both of these issues are relevant in this review. First, as noted above, we know that two systematic reviews found very few interventions targeted at primary care practitioners to improve the screening and referral of adults with obesity [ 25 , 27 ], though these are now a number of years old, and this is clearly an area where new research is being produced on a regular basis [ 17 , 37 ]. Second, we know from similar research into interventions targeted at primary care practitioners to improve identification and referral in sensitive areas - in this case intimate partner violence screening [ 38 ] - that there are a number of different potential intervention components (for example effective protocols, ongoing training, feedback, improving access to support), which may in turn have different mechanisms underpinning them (for example practitioner self-efficacy, trust and confidence in the service, accepting responsibility).…”
Section: Methodsmentioning
confidence: 99%
“…This is a time commitment that most GPs and PNs would be unable to make. More recently, attention has turned towards the use of brief interventions for weight management in primary care, building on the successful use of brief interventions for smoking cessation or alcohol [ 17 ]. It remains to be seen how transferrable such an approach might be in the context of weight management, as there are significant qualitative differences between the discussion of a patient’s weight and that of their smoking or alcohol intake, as the following barriers demonstrate.…”
Section: Introductionmentioning
confidence: 99%